Comparison of SAW methods with WP method laptop recommendations - Ahmad Taufik Marsaoly; Riffa Haviani Laluma (Jurnal Mandiri IT, 2023)
In this era, laptop users are increasing rapidly to support people's work. Various types and brands of laptops have been produced and distributed on the Indonesian market with various specifications and different uses. Survey results from indonesiabaik.id show that the use of laptops without internet for work is 54.55%. Meanwhile, laptops used for entertainment were 34.94%. With various types, specifications and uses of laptops having varying prices from cheap to expensive, this creates a dilemma for people in choosing a laptop that suits their needs. Many people have already bought laptops, but the increasing demand ends up having to buy another laptop to suit the increasing work and entertainment needs. The method used for comparison is the SAW method with the WP method in a web-based application that can recommend laptops. The results of this research show that recommending laptops using the SAW method or the functionally WP method is very helpful in finding out the overall ranking or level of the laptop. However, in terms of effectiveness, the SAW method still has the possibility of having the same ranking value and that could cause a dilemma for people in determining the ranking order on laptops. Meanwhile, the WP method has the possibility of the same ranking value being very small so it can determine the laptop ranking order better than the SAW method. From the overall comparison, it can be concluded that the WP method is better in recommending laptops.